Rural sustainable development policies in the Kurdistan Region of Iraq and their impact on migration - Nanakali, Hemna A. Mawlood (Technische Universität Dortmund, 2021)
Rural migration in Kurdistan Region has occurred in two different patterns as a result of two different policies. The first pattern was a forced migration by a policy of the Iraqi government. This policy resulted in total demolition and evacuation of 4000 villages and lasted between five to 17 years, depending on the area. In contrast, the second migration was a consequence of push and pull factors. After the approval of the new investment law by the Kurdistan Region Government in 2006, this region was quickly developed and several sectors were significantly improved, such as the oil and construction sectors which pulled labour force everywhere to different sectors. However, the agricultural sector was not that much in the focus of the government and investors as compared like the other sectors. Hence, this development caused significant rural to urban migration and had severe adverse impacts, even ruin, for agricultural projects. This study describes the size of the demolition, and additionally investigates the most effective factor for migration after 1991. On the other hand, the study also explains how the government dealt with this phenomenon. The study employed a mixed-methods research design involving archival methods for the extent of the demolition. Furthermore, questionnaires were administered to 330 migrants and non-migrants (165 migrants in Mergasur and 165 non-migrants in Bahrka) to test the conceptual framework and the hypotheses. This was followed by an in-depth interview with 20 villagers and farmers to explore the push and pull factors in both origin and destination places. The last step in the research process were the expert interviews. These interviews were conducted with six persons at different levels from top management to low managerial level. The analysis revealed that the general effects of migrations in the rural areas were mixed. While migrations have had negative or positive impacts for some, they have also impacted on work culture, family size, lifestyle and education level. There were various factors such as physical security, income and other factors related to income that were the main factors impacting on migration after 1991. The factor of income was more deeply defined in this study as a “secured satisfied income”, which is addressed at a minimum by the Critical income level (CIL). The study concluded that the CIL is $137 and can be reached via proper policies in a proper conceptual framework.
The case of Erbil Governorate
Keywords: Kurdistan; Migration; Rural sustainable development; Policy-making; 710; Kurdistan; Politische Entscheidung; Migration; Landflucht